Preliminary evidence of mindsets and training satisfaction in Malaysia - Fontaine, Rodrigue Ancelot Harvey; Elkheloufi, Abderrahmane (Malaysian Institute of Management, 2015)
Dweck (2008) argues that individuals have a fixed or a growth mindset, which influences individuals’ effort, commitment, resilience, and learning. A critical aspect of Dweck’s work is that changing people’s mindset is a straightforward process. It can often be achieved with a 15 minutes briefing at the beginning of a workshop. This paper hypothesises that the mindset will influence the perceived satisfaction with training and development programmes. Through a survey of 100 employees, the study found a positive relationship between mindset and training satisfaction (r=0.435**).